TIPE KOMITMEN PERNIKAHAN PADA TIGA PASANG SUAMI ISTRI USIA REMAJA YANG HAMIL DI LUAR NIKAH - Rouwi Girlina Astri; Shanty Sudarji (Psibernetika, 2016)
Early marriage by teenagers due to pregnancy before married have a high risk of divorce, because teenagers are not ready economically, physically and mentally yet in building family. But the risk of divorce can be avoided if there is a marriage commitment, because commitment related with better communication, greater happiness and constructive behavior when facing difficulties. Marriage commitment is a subjective experience where both husband and wife want to keep the marriage in bad and good times, feeling morally have to stay married, and forced to remain in marriage. This research used a qualitative method with phenomenology approach, with interviews and observations method to collect data. This research conduct to three pairs of husband and wife with an age range of 16 to 22 years old who married because of pregnancy before married, with age of marriage minimum three years and maximum ten years. The result showed that three couple of subjects fulfilled personal type of marriage commitment, and at the same time, three of them also fulfilled moral type of marriage commitment. The households of three couple of subjects could be a living example that marriage could survive by having marriage commitment eventhough the marriage itself didn’t start with the proper way as the culture and norm said. It could be the same way with the marriage which didn’t cause by pregnancy before married, so that the divorce inIndonesia could be avoided. Keywords : marriage commitment, teenagers, early marriage, pregnancy before married